PENGARUH ENVIRONMENTAL DISCLOSURE, SOCIAL DISCLOSURE, PROFITABILITAS, DAN FAKTOR LAIN TERHADAP NILAI PERUSAHAAN - YOSSY APRIL SARI KAWI; KARTINA NATALYLOVA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research is conducted to determine the effect of environmental disclosure, social disclosure, profitability, dividend payout ratio, firm size, liquidity, and leverage towards the firm value. The object of this research is non-financial companies that listed on the Indonesia Stock Exchange from 2018 to 2020. This research use the purposive sampling method to selecting the sample, there are 98 non-financial companies listed on the Indonesia Stock Exchange from 2018 to 2020 as the research sample. Multiple linear regression model was used as a method of data analysis. The results of this research indicate that profitability, dividend payout ratio and firm size have an impact toward firm value, this explains that the higher the of profitability obtained by the company, and the higher of dividend distribution to shareholders, performance of company’s will be higher too. While other variables, namely environmental disclosure, social disclosure, liquidity, and leverage have no effect toward firm value.